Algorithm and Program for Calculation and Analysis of Modes and Losses of Electric Energy in Electricity Distribution Networks of 6–20 kV - M. I. Fursanov; S. G. Gapaniuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A refined mathematical model and algorithm for operative control of the modes and detection of energy loss sites in electricity distribution networks of 6–20 kV have been developed in the paper. The developed software program can be used for testing other technical solutions and computer programs pertaining to the area of research and it is considered as one of the most important components applied for creation of intellectual electric networks.